Family, faith and fortification: Yorkshire 1066-1250 - Speight, Sarah (1993)
This thesis is an examination of the tenure and charitable donations of a number of interconnected noble families in post-Conquest Yorkshire. It begins with an introduction to the region; a social and political area of midland and northern England as opposed to a 'county' limited by set boundaries. The types of evidence are explained, charters, chartularies and surviving buildings, before moving on to the historical background.